2017
DOI: 10.1155/2017/7212985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Protective Effects of Individual Components of Particulatedtrans-Sialidase (PTCTS), PTC and TS, against High Cholesterol Diet-Induced Atherosclerosis in Rabbits

Abstract: Previous studies showed the presence of Mycoplasma pneumoniae (M. pneumoniae) and membrane-shed microparticles (MPs) in vulnerable atherosclerotic plaques. H&S Science and Biotechnology developed PTCTS, composed by natural particles from medicinal plants (PTC) combined with trans-Sialidase (TS), to combat MPs and Mycoplasma pneumoniae. Our aim was to determine the effects of the different components of PTCTS in a rabbit model of atherosclerosis. Rabbits were fed with high cholesterol diet for 12 weeks and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Moreover, several experiments in vitro showed that desialylation of native LDL with trans-sialidase makes it capable of inducing accumulation of cholesterol in cells in the same way, as in patients affected with atherosclerosis [78,79]. Apart from human atherosclerotic plaques, trans-sialidase showed positive effects influencing atherosclerosis regression in the rabbit model of atherosclerosis [80]. The studies indicated that there is a difference between the activity and specificity of sialidases in atherosclerotic lesions and unaffected intima [81].…”
Section: The Role Of Sialidases In Atherosclerosismentioning
confidence: 99%
“…Moreover, several experiments in vitro showed that desialylation of native LDL with trans-sialidase makes it capable of inducing accumulation of cholesterol in cells in the same way, as in patients affected with atherosclerosis [78,79]. Apart from human atherosclerotic plaques, trans-sialidase showed positive effects influencing atherosclerosis regression in the rabbit model of atherosclerosis [80]. The studies indicated that there is a difference between the activity and specificity of sialidases in atherosclerotic lesions and unaffected intima [81].…”
Section: The Role Of Sialidases In Atherosclerosismentioning
confidence: 99%
“…Treatments based on the use of natural nanoparticles were also found to be effective in reducing the number of plasma MPs. For instance, Garavelo et al [153] reported recently that the treatment of a rabbit model of atherosclerosis, fed a high-cholesterol diet, with natural nanoparticles obtained from medicinal plants (PTC) combined with trans-Sialidase (TS) for 6 weeks, reduced the number of total MPs in addition to those positive for Mycoplasma pneumoniae and oxidized LDL. Furthermore, the treatment of animals with PTC and TS reduced atherosclerotic plaque area and caused a positive remodeling of ascending aortic segment [153].…”
Section: Future Directionsmentioning
confidence: 99%
“…Numerous pathogens have been identified as contributing factors to the chronic inflammatory state of atherosclerosis such as Coxsackie B virus, HIV, H.pilori, CMV (2, 3). In this general comment we develop the concept about mechanism of PTCTS works, a new anti-oxidant natural nanoparticles (PTCTS) for decreasing the amount of atherosclerotic plaques, possibly due to removal of infectious agents (4).…”
mentioning
confidence: 99%
“…The Nutricosmetic with PTCTS, combining transialidase enzyme with nanoparticles derived from orchid extracts, was able to remove archaea. This nutricosmetic agent in experimental work with atherosclerotic rabbits lead to reduction of inflammation in plaques in parallel with removal of microvesicles from serum arteries, without side effects (4, 21).…”
mentioning
confidence: 99%